Biofilm formation to inhibition: role of zinc oxide-based nanoparticles - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Badiger, Manohar V.; Patel, Pratikshkumar R.; Thorat-Gadgil, Bhagyashi S.; Pandit, Abhay; Bohara, Raghvendra A. (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Zinc oxide nanoparticles have received much attention worldwide as they possess unique properties like varied morphology, large surface area to volume ratio, potent antibacterial activity, and biocompatibility. Biofilm contains homogenous or heterogeneous microorganisms that remain enclosed in a matrix of an extracellular polymeric substance on biotic or abiotic surfaces. Bacterial biofilm formed on medical devices such as central venous catheters, urinary catheters, prosthetic joints, cardiovascular implantable devices, dental implants, contact lenses, intrauterine contraceptive devices and breast implants cause persistent infections. Such biofilm-associated infections in medical implants cause serious problems for public health and affect the function of medical implants. So, there is an urgent need for the use of an antimicrobial agent that will inhibit biofilm, including such antibiotic-resistant bacterial strains as bacteria, to develop multiple drug-resistances resulting in failure of the antibiotic's action. The antimicrobial agent used should be ideal in terms of biocompatibility, antimicrobial activity, stability at different environmental conditions, with less sensitivity to the development of resistance towards micro-organisms, safe for in vivo and in vitro use, and remain non-hazardous to the environment, etc. The first objective of the review discusses the insights into the formation of biofilm on a medical device with the current strategies to inhibit. The second purpose is to review the recent progress in ZnO- based nanostructure including composites for antibacterial and anti-biofilm activities. This will offer a new opportunity for the application of Zinc oxide-based material in the prevention of biofilm on the medical devices.
Keywords: antibacterial activity; Antibiofilm agent; Biocompatibility; Biofilm; Nanocomposites; ZnO nanoparticles